HIGH RESOLUTION RP-HPLC METHOD FOR THE DETERMINATION OF HYPERTENSIVE DRUG PRODUCTS - PHANI.R.S.CH,; K.R.S. PRASAD,; USENI REDDY MALLU, (International Journal of Pharma and Bio Sciences, 2013)
To develop a RP-HPLC method for the simultaneous determination of eight active ingredients including hydrochlorothiazide (HCTZ), metoprolol succinate, valsartan, losartan Potassium, benazepril hydrochloride, telmisartan, amlodipine besylate and atorvastatin in pharmaceutical products. METHOD: HPLC analysis was carried out by using a XTerra C18 column with the gradient mobile phase composed of Sol-A: ammonium acetate buffer (1.4g of ammonium acetate in to 1000ml of HPLC water) and sol-B: acetonitrile with simple gradient program (0-5min, sol-A:88-85; 5-10min- sol-A:85-70; 10-18min- sol-A:70-70; 18-25min- sol-A:70-55; 25-30min- sol-A:55-88 and 30-35min- sol-A:88-88). Flow for mobile phase elution is 1.0ml per min; column oven temperature is maintained at 35°C and record the absorbance with 230nm.RESULT: The co-relation coefficient for all eight active ingredients is not less than 0.999. The average recoveries of the all components were 98.0% to 102.0%.CONCLUSION: This HPLC method is simple, quick and reproducible, with high recovery and has been successfully applied to the simultaneous determination of the eight components in pharmaceutical drug products.